Iodide‐Catalyzed Ring‐Opening Cyclization of Cyclohexane‐1, 3‐dione‐2‐spirocyclopropanes. Issue 15 (27th June 2018) - Nambu, Hisanori; Onuki, Yuta; Ono, Naoki; Yakura, Takayuki
Abstract: The ring‐opening cyclization of 2′, 3′‐nonsubstituted and 2′‐electron‐withdrawing group (EWG)‐substituted cyclohexane‐1, 3‐dione‐2‐spirocyclopropanes was accomplished using iodide as a catalyst. The nonsubstituted derivatives afforded 3, 5, 6, 7‐tetrahydro‐1‐benzofuran‐4(2 H )‐ones in high yields in the presence of trimethylsilyl iodide at room temperature. The EWG‐substituted spirocyclopropanes, in turn, underwent regioselective ring opening followed by cyclization, which gave rise to 2‐substituted tetrahydrobenzofuran‐4‐ones when a combination of tetrabutylammonium iodide catalyst and trifluoromethanesulfonic acid was used, whereas calcium iodide afforded the 3‐substituted derivatives. Abstract :